Comparative analysis of phytoplankton dynamics and water quality assessment in selected lentic water bodies of Haryana, India - Pooja Devi; Anita Bhatnagar (Environment Conservation Journal, 2023)
The study was designed to assess the water quality based on physico-chemical parameters and phytoplankton communities of eight lentic water bodies of Haryana which are famous for mass bathing and religious rituals taking place here. To evaluate comparative analysis of composition, diversity and distribution of Phytoplankton and physico-chemical factors, water samples were collected seasonally viz., summer, monsoon, post monsoon and in winters from all the eight sites in triplicate. Total 118 phytoplankton taxa were observed at all sites. Among these cyanophyceae group was found most dominant at sites 1, 2, 4, 5, 7, 8 whereas cholorophyceae at site 6, bacillariophyceae at site 1,3,4,7 whereas xanthophyceae was in abundance at site 5. Population density (nos. L-1) wise phytoplankton trend was Cyanophyceae > Chlorophyceae > Bacillariophyceae >Desmidiaceae and Species diversity wise phytoplankton trend observed was Chlorophyceae > Bacillariophyceae > Cyanophyceae >Desmidiaceae. Correlation of different phytoplankton groups with physicochemical factors revealed a significant negative correlation of Cyanophyceae with pH, whereas a significant positive correlation of ortho-phosphate with Desmids and bacillariophyceae wheareas CO2 showed a positive correlation with Xanthophyceae.  Appearance of pollution tolerant taxa of phytoplankton Microcystis aeruginosa, Phormidium sp., Scenedesmus spp., Pediastrum spp., Mougeotia sp., Synedra sp., Pediastrum spp. at most of the sites indicated the sign of the more organic pollution and degradation in the water quality of the selected sites due to religious immersion, mass bathing and by other anthropogenic activities. Suitable remedial actions should be adopted by regulatory bodies and policy makers to maintain the water quality of these aquatic systems.